Prevalence of arrhythmias on the long term of adult patients with partial anomalous pulmonary venous connection treated surgically and conservatively: data from the SACHER registry and a French center. (25th November 2020) - Touray, M; Bouchardy, J; Ladouceur, M; Schwerzmann, M; Greutmann, M; Tobler, D; Harald, G; Engel, R; Pruvot, E; Blanche, C; Sekarski, N; Rutz, T
Abstract: Introduction: Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital heart disease, characterized by one or some but not all pulmonary veins anomalously connected to the right atrium or a systemic vein. PAPVC is either an isolated shunt lesion or associated with an atrial septal defect (ASD). This study compares the arrhythmic outcome of patients treated surgically with those clinically monitored. Method: Clinical, surgical, imaging and invasive data of PAPVC patients were retrospectively reviewed from 7 centers from the Swiss Adult Congenital HEart disease Registry (SACHER) and one French center. Results: A total of 168 patients with PAPVC were identified. Most (77%) patients underwent surgery, while the remaining (23%) ones were treated conservatively with clinical monitoring. The operated group (OG) had a significantly higher number of associated ASD (N=106, 82%) (p<0.001) and a higher number of anomalous pulmonary veins leading to a mean Qp:Qs at 2.5±1.2 before surgery (table). Moreover, the majority of patients in the OG had cardiac symptoms (N=78, 60%) and were diagnosed at a significantly younger age (table). Mean age at operation was 27±20 years. Age did not differ at latest follow-up (table). Holter recordings revealed a higher prevalence of arrhythmia in the OG (p=0.031), mainly of supraventricular tachyarrhythmias (table). The occurrence of ventricular non-sustained tachycardia and of bradyarrhythmia did not statistically differ between groups. Patients in the OG required more often medical treatment for arrhythmias: 12 (9%) needed electrophysiological study in the OG and none in the NOG (p=0.057). The amount of patients requiring a pacemaker implantation in the OG (11%) was significantly higher than that of NOG (0%) (p=0.039). Conclusion: Patients after PAPVC repair present with a significant higher burden of arrhythmia than conservatively treated patients, either due to a larger shunt pre-operatively and/or as a late complication of the corrective surgery itself. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Unrestricted grant from Actelion, Switzerland